The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.2355/isijinternational.isijint-2018-580
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nut Coke Addition on Physicochemical Behaviour of Pellet Bed in Ironmaking Blast Furnace

Abstract: One of the primary causes that limit the blast furnace productivity is the resistance exerted to the gas flow in the cohesive zone by the ferrous burden. Use of nut coke (10-40 mm) together with ferrous burden proves beneficial for decreasing this resistance. In present study, effect of nut coke addition on the olivine fluxed iron ore pellet bed is investigated under simulated blast furnace conditions. Nut coke mixing degree (replacement ratio of regular coke) was varied from 0 to 40 wt% to investigate the phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 16 publications
(28 reference statements)
0
29
0
Order By: Relevance
“…It was found that the nut coke addition in the pellet bed improves the bed permeability substantially. 16) Furthermore, the cohesive zone temperature range was observed to reduce by 16°C for every 10 wt% nut coke addition. 16) In the study, it was suggested that along with enhanced reduction kinetics, the higher iron carburisation would be the main cause for such behaviour.…”
Section: Melting Behaviour Of Iron Ore Pellet Bed Under Nut Coke Mixementioning
confidence: 92%
See 4 more Smart Citations
“…It was found that the nut coke addition in the pellet bed improves the bed permeability substantially. 16) Furthermore, the cohesive zone temperature range was observed to reduce by 16°C for every 10 wt% nut coke addition. 16) In the study, it was suggested that along with enhanced reduction kinetics, the higher iron carburisation would be the main cause for such behaviour.…”
Section: Melting Behaviour Of Iron Ore Pellet Bed Under Nut Coke Mixementioning
confidence: 92%
“…16) Furthermore, the cohesive zone temperature range was observed to reduce by 16°C for every 10 wt% nut coke addition. 16) In the study, it was suggested that along with enhanced reduction kinetics, the higher iron carburisation would be the main cause for such behaviour. However, the complete characterisation was not presented and discussions were not made about melting pattern in the presence or absence of nut coke in the pellet bed.…”
Section: Melting Behaviour Of Iron Ore Pellet Bed Under Nut Coke Mixementioning
confidence: 92%
See 3 more Smart Citations